CORPORATE GOVERNANC, CORPORATE SOCIAL RESPONSIBILITY DAN KETAHANAN PERUSAHAAN DI INDONESIA: CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY AND CORPORATE RESILIENCE IN INDONESIA - Asniati Bahari; Khalilul Rahman (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study aims to provide empirical evidence about the influence of internal corporate governance mechanisms and corporate social responsibility on corporate resilience. This research's novelty is to analyze companies' resilience during the Covid-19 pandemic in Indonesia from March to September 2020. Data analysis in this study used SmartPLS 3.3.9 software. Based on the purposive sampling technique, a sample of 44 companies was obtained, which were registered at IDX80 as of February 2020. The findings of this study are that CSR on the topic of Environment does not have a significant effect on corporate resilience; however, Economic and Social topics have a significant effect on corporate resilience. Corporate governance on the board of commissioners and directors has no significant effect on corporate resilience, but the audit committee significantly affects corporate resilience. Other findings in this study indicate that Firm Size and Sales Growth significantly affect corporate resilience. The results of this study help investors and management understand the importance of CG, CSR, Firm Size, and Sales Growth in building corporate resilience in facing the coming crisis.